Facile Azabenz‐Annulations through UV‐induced Photocyclization: A Promising Method for Perylenediimide‐Based Organic Semiconductors. Issue 3 (30th December 2021) - Sun, Hua; Mu, Zifeng; Yang, Canglei; Zhang, Kai; Ji, Xingyu; Zhang, Tianshu; Ding, Huanda; Wang, Shifan; Dong, Liming; Zhang, Jing; Zhang, Qichun
Abstract: The derivatization of perylenediimides (PDIs) by bay decoration is essential for the development of PDI‐based semiconductors owing to their excellent photoelectric properties. Herein, four bis‐azabenz‐annulated PDIs (bis‐AzaBPDIs) are concisely synthesized in high yields through ultraviolet‐induced photocyclization, where the reaction processes including aldimine condensation, cyclization, and oxidative re‐aromatization are investigated. The optical characterizations and theoretical simulation reveal that the unique properties of the four bis‐AzaBPDIs are comparable to their parent PDI. Organic field effect transistors with compounds 2, 3, or 4 as active layers indicated that all compounds showed unipolar electron transport properties with the mobilities of 1.1×10 −3, 5.8×10 −4, and 8.5×10 −6  cm 2  V −1  s −1, respectively. These results suggest the great potential of bis‐AzaBPDIs as organic semiconductors. The easy preparation approach reported in this work would renew research interest in developing bis‐AzaBPDI‐based optoelectronic molecules. Abstract : A series of bis‐azabenz‐annulated perylenediimides (bis‐AzaBPDIs) are concisely synthesized in high yields through ultraviolet‐induced photocyclization with only a catalytic amount of I2 . The unique optical properties and organic field effect transistor performances indicate the great potential of bis‐AzaBPDIs as organic semiconductors.